Sustaining Universal Health Coverage in France : A Perpetual Challenge - Barroy, Helene (World Bank Group, Washington, DC, 2014)
While universal health coverage (UHC) offers a powerful goal for a nation, all countries-irrespective of income are struggling with achieving or sustaining UHC. France is a high-income country where HC is in effect universal. Health-related costs are covered by a mix of mandatory social health insurance (SHI) and private complementary schemes, while benefit packages are comprehensive, uniform, and of good quality. France provides some of the highest financial protection among countries in the Organization for Economic Co-operation and Development (OECD). Still, under pressure to sustain UHC without compromising equity of access, the system has been fine-tuned continually since inception. Much can be learned from France's experience in its reforms toward better fiscal sustainability, equity, and efficiency. The main purpose of the study is to assess major challenges that France has faced for sustaining UHC, and to share its experiences and lessons in addressing system bottlenecks to benefit less developed countries as they embark on the path to UHC.